REAKTUALISASI DAKWAH WALISONGO PADA ERA KONSUMTIF MEDIA SOSIAL - KIFAYAH, NURUL; NIAMAH, LUTHFI ULFA (TASAMUH, 2021)
The current millennial era, which has brought the flow of globalization, has led to changes in the patterns of life and attitudes of the Indonesian people to create traditions or cultures that have begun to be displaced by the current trends. However, in the history of Islamic da'wah the journey of Wali Songo's da'wah was not easily abandoned or forgotten by the Indonesian people, especially by Muslims throughout Indonesia. Although there are different generations of Wali Songo's da'wah strategies are still preserved today, this is because Wali Songo's preaching was conveyed in a peaceful way and made use of the existing culture at that time as a medium of preaching so that it was easier to get a place in the hearts of the people. The challenge of preaching during the Wali Songo era with the consumptive era of social media has also been different, if the preaching of Wali Songo is the challenge of preaching the community's beliefs that have already been believed, while the challenge of preaching in the consumptive era of social media is more on the commitment of the people in maintaining Islamic values in facing the very strong external cultural influences, so that a preacher must be smarter in following the current trend without getting carried away in it.